Soldados da borracha na era Henry Ford no município de Belterra: um recorte histórico dos anos de 1934 a 1945 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The article in question presents a historical cut between the years 1934 to 1945, on the Rubber Soldiers in the Henry Ford era in the town of Belterra. The study aimed to understand the importance of rubber soldiers in the formation of the Belterrense population during the period of territorial occupation of the municipality, its cultural manifestations, economic, political and social relations. In order to do so, the material preserved in the Memory Center in the municipality of Belterra was used as a source of research, as documents, photographs and newspapers that portrayed the history of rubber soldiers in the beginning of the 20th century in that municipality, as well as interviews with rubber soldiers who still live in that place and who during a certain period of history were part of the scenario of rubber and its extraction here in the state of Pará.
Keywords: Recorte Histórico; Soldados da Borracha; Belterra; Henry Ford.; CNPQ:: CIÊNCIAS HUMANAS